Increased CD112 expression in methylcholanthrene-induced tumors in CD155-deficient mice. - Yoko Nagumo (PLoS ONE, 2014)
Tumor recognition by immune effector cells is mediated by antigen receptors and a variety of adhesion and costimulatory molecules. The evidence accumulated since the identification of CD155 and CD112 as ligands for DNAM-1 in humans and mice has suggested that the interactions between DNAM-1 and its ligands play an important role in T cell- and natural killer (NK) cell-mediated recognition and lysis of tumor cells. We have previously demonstrated that methylcholanthrane (MCA) accelerates tumor development in DNAM-1-deficient mice, and the Cd155 level on MCA-induced tumors is significantly higher in DNAM-1-deficient mice than in wild-type (WT) mice. By contrast, Cd112 expression on the tumors is similar in WT and DNAM-1-deficient mice, suggesting that CD155 plays a major role as a DNAM-1 ligand in activation of T cells and NK cells for tumor immune surveillance. To address this hypothesis, we examined MCA-induced tumor development in CD155-deficient mice. Unexpectedly, we observed no significant difference in tumor development between WT and CD155-deficient mice. Instead, we found that Cd112 expression was significantly higher in the MCA-induced tumors of CD155-deficient mice than in those of WT mice. We also observed higher expression of DNAM-1 and lower expression of an inhibitory receptor, TIGIT, on CD8+ T cells in CD155-deficient mice. These results suggest that modulation of the expression of receptors and CD112 compensates for CD155 deficiency in immune surveillance against MCA-induced tumors.